Family Spillover Effects of Marginal Diagnoses: The Case of ADHD - Petra Persson; Xinyao Qiu; Maya Rossin-Slater (Institute of Labor Economics (IZA), 2021)
The health care system commonly relies on information about family medical history in the allocation of screenings and in diagnostic processes. At the same time, an emerging literature documents that treatment for "marginally diagnosed" patients often has minimal impacts. This paper shows that reliance on information about relatives' health can perpetuate marginal diagnoses across family members, thereby raising caseloads and health care costs, but without improving patient well-being. We study Attention Deficit Hyperactivity Disorder (ADHD), the most common childhood mental health condition, and document that the younger siblings and cousins of marginally diagnosed children are also more likely to be diagnosed with and treated for ADHD. Moreover, we find that the younger relatives of marginally diagnosed children have no better adult human capital and economic outcomes than the younger relatives of those who are less likely to be diagnosed. Our analysis points to a simple adjustment to physician protocol that can mitigate these marginal diagnosis spillovers.
Keywords: I14; I18; J13; 330; ADHD; targeting; marginal diagnosis; mental health; family spillovers